Childhood Abuse Increases Risk of Adverse Perinatal Outcomes [22F]. (May 2018) - Johnson, Quinetta; Bush, Heather; Coker, Ann
Abstract : INTRODUCTION: Intimate partner violence (IPV) has been associated with numerous adverse perinatal outcomes. Little is known, however, regarding the impact of childhood abuse on subsequent adverse pregnancy outcomes among women never experiencing IPV. METHODS: Data from the University of Kentucky's Women's Health & You cohort were used to assess the association between women who experienced childhood sexual (CSA) and/or physical (CPA) abuse and the self-reported history of third trimester bleeding, postpartum depression, preterm labor, preeclampsia, and gestational diabetes. Multivariate logistic regression modeling was used to determine rate ratios (RR) for women who had never experienced IPV. Childhood abuse was categorized as experiencing both sexual and physical abuse, sexual abuse 'alone', and physical abuse 'alone'; the comparison group were women never experiencing abuse. RESULTS: Among the 12, 507 ever pregnant participants, 21% reported postpartum depression, 7.0% reported bleeding in their 3rd trimester, 12.3% disclosed preeclampsia, 16.0% reported preterm labor, and 8.2% had gestational diabetes. CSA and CPA alone were both statistically significantly (P<.05) associated with an increased risk of 3rd trimester bleeding, preterm labor, and postpartum depression. Those experiencing both CSA and CPA were at an increased risk of all five outcomes with the highest RR of 2.05 (95% CI 1.30-3.23) for 3rd trimester bleeding and 1.95 (95% CI 1.54-2.43) for postpartum depression. CONCLUSION: Childhood sexual and/or physical abuse were both associated with multiple adverse perinatal outcomes. Because both forms of abuse have adverse perinatal impact, screening for such abuse and tailoring a woman's prenatal care may improve maternal and neonatal outcomes.